A CRIANÇA COM SÍNDROME DE CORNÉLIA DE LANGE NA EDUCAÇÃO INFANTIL: UM ESTUDO DE CASO - Perovano, Maycon de Oliveira (2020)
This research aimed to investigate the process of learning, development and inclusion of a child with Cornelia de Lange syndrome in early childhood education. The research uses as methodology the case study of the ethnographic type, having as theoretical